Pengaruh Praktik Good Governance Terhadap Kualitas Pelayanan KTP di Kantor Kecamatan Tiroang Kabupaten Pinrang: Analisis Kuantitatif - Wahyuni, Wahyuni; Ahmad, Jamaluddin; Sundari, Sundari (Policy, Law and Political Research Center, 2025)
This study aims to determine the Effect of Good Governance Practices on the Quality of KTP Services at the Tiroang District Office, Pinrang Regency: Quantitative Analysis, and to find out. This research method approach uses a quantitative descriptive approach. The population in this study were 97 people in Tiroang sub-district. The sample technique used was incidental sampling. The data collection techniques used in this study were observation, questionnaires, and literature studies. The data collected were then processed and analyzed using quantitative descriptive analysis techniques and simple linear regression analysis with the help of descriptive statistics using SPSS and a Likert scale. The results showed that the practice of good governance in the tiroang sub-district office was categorized as good with the percentage results: a) Transparency 64.6%, b) Accountability 63.2%, c) Participation 65.4%, d) Rule of Law 62.8%, e) Effectiveness and Efficiency 64.2%, f) Equality and Inclusiveness 61.8%, g) Responsiveness 66.4%, h) Consensus-Oriented 66%, i) Strategic Vision 63.6%, with an average of 63.6%. Strategic Vision 63.6%, with an average percentage of 64.2%. While the quality of KTP services at the tiroang sub-district office is categorized as good with the percentage results of a) Physical Evidence 63.4%, b) Reliability 63.8%, c) Responsiveness 64.2%, d) Guarantee 63.2%, e) Attention 63%, with an average percentage of 63.5%.